Clinical Performance of Three Commercial SARS‐CoV‐2 Rapid Antigen Tests for Community-Dwelling Individuals in a Tropical Setting - Morales-Jadán, Diana; Viteri-Dávila, Carolina; Castro-Rodriguez, Bernardo; Vallejo-Janeta, Alexander Paolo; Rivera-Olivero, Ismar A.; Perez, Franklin; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2022)
During the second year of the COVID-19 pandemic, the use of Rapid Diagnosis Antigen Tests (RDAgTs) for SARS-CoV-2 detection has substantially increased as some of the brands available in the market were certified for clinical use by international regulatory agencies. RDAgTs are a fast and cheap tool for SARS-CoV-2 surveillance with great potential to improve testing capacities in middle- and low-income countries compared to the gold standard RT-qPCR. However, as the clinical performance of RDAgTs has been shown to vary greatly between the commercial brands available, evaluation studies are necessary. Moreover, the available evaluation has been done in high-income countries while SARS-CoV-2 transmission is also actively happening in developing countries, many of which are located in tropical latitudes where cross-reactivity with other infectious agents is highly prevalent, which could compromise RDAgT specificity. Moreover, unreported mutations and/or new SARS-CoV-2 variants may compromise RDAgT sensitivity as genomic surveillance is limited in these settings. Here we describe a multicenter and manufacturer‐independent evaluation of the clinical performance and analytical sensitivity of three different RDAgTs brands available in South America from three companies, Rapigen (South Korea), SD-Biosensor (South Korea), and Certest (Spain), compared to the gold standard RT-qPCR. A total number of 1,646 nasopharyngeal swabs from community-dwelling individuals were included in the study, and 379 of them were SARS-CoV-2 positive by RT-qPCR. The overall sensitivity for each RDAgT was 79% (IC95%: 72 - 86.2), 64.2% (IC95%: 56.7 - 71.6), and 45.8% (IC95%: 35.8 - 55.8) for SD-Biosensor, Certest, and Rapigen, respectively. The overall specificity for each RDAgT was 100%, 97.7% (IC95%: 96.8 - 98.6), and 100% for SD-Biosensor, Certest, and Rapigen, respectively. However, the limit of detection (LoD) to achieve a sensitivity over 90% was substantially lower for Certest RDAgT (102 copies/uL) compared to SD-Biosensor (103 copies/uL) or Rapigen (106 copies/uL) RDAgTs, considering that the gold standard RT-qPCR method used in this study has a high sensitivity of 97.7% and low LoD of 5 copies/uL. Additionally, the Certest RDAgT also showed an improved sensitivity up to 79.7% (IC95%: 70.2 – 89.2) for symptomatic individuals. Finally, the slight reduction in specificity for Certest RDAgTs was only associated with one of the laboratories performing this study, pointing out the need for locally assessed evaluation for RDAgTs like this one carried out in Ecuador. In conclusion, two of the three the RDAgTs tested in this study are a fast, cheap, and point of care tool for SARS-CoV-2 surveillance and reliable enough to detect SARS-CoV-2 infectious individuals.